The Impact of Physical Exercise on College Students’ Physical Self-Efficacy: The Mediating Role of Psychological Resilience - Wentao Qiu; Xishuai Wang; Hongcheng Cui; Wenxue Ma; Haibin Xiao; Guofeng Qu; Rong Gao; Fangbing Zhou; Yuyang Nie; Cong Liu (Behavioral Sciences)
The mental health of college students has become a key focus in higher education, and physical activity may play a crucial role in promoting positive psychology among college students. This study explores the relationship between physical activity and physical self-efficacy among college students and analyzes the mediating effect of psychological resilience to provide theoretical support for health intervention strategies. This study included a sample of 369 college students aged 18–25 from the Zhuhai Campus of Beijing Normal University. The International Physical Activity Questionnaire-Short Form (IPAQ-S), the Connor-Davidson Resilience Scale (CD-RISC), and the Physical Self-Efficacy Scale for College Students (PSES-CS) were administered to 369 students (138 males and 231 females) through a questionnaire survey. The data were processed using SPSS 29.0 and AMOS 26.0 software. Significant positive correlations were found between physical activity, psychological resilience, and physical self-efficacy. Regression analysis revealed that physical activity had a significant effect on psychological resilience and physical self-efficacy and explained 8.3% and 14.9% of the variance, respectively. Psychological resilience partially mediated the relationship between physical activity and physical self-efficacy, accounting for 30.05% of the total effect. Moreover, gender moderated the relationship between physical activity and physical self-efficacy. Physical activity can enhance the physical self-efficacy of college students, with psychological resilience playing a partial mediating role and gender acting as a moderating factor. Emphasizing the cultivation of psychological resilience in educational and personal growth processes is highly important for improving individuals’ physical self-efficacy and well-being.